1990
DOI: 10.1093/jnci/82.19.1539
|View full text |Cite
|
Sign up to set email alerts
|

Primary Chemotherapy To Avoid Mastectomy in Tumors With Diameters of Three Centimeters or More

Abstract: In 165 women with breast cancer who were candidates for mastectomy because the largest diameter of the tumor was 3 cm or more, we administered primary chemotherapy in the attempt to substitute conservative for mutilating surgery. We then systematically quantitated tumor reduction by clinical, radiologic, and histopathologic evaluations. Five consecutive groups of 33 patients received cyclophosphamide, methotrexate, and fluorouracil (CMF); fluorouracil, doxorubicin (Adriamycin), and cyclophosphamide (FAC); or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
233
1
28

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 575 publications
(273 citation statements)
references
References 0 publications
11
233
1
28
Order By: Relevance
“…This apparently worse response rate to chemotherapy after failed hormone therapy has also been noted in metastatic disease (Swenerton et al, 1979). Impaired response to chemotherapy in untreated ER-moderate/ -rich tumours has been previously noted (Bonadonna et al, 1990;Mauriac et al, 1991;Belembaogo et al, 1992). However, the known effects of hormone therapy upon breast cancer could further prejudice the subsequent response to chemotherapy.…”
Section: Response To Primary Hormone Therapymentioning
confidence: 96%
“…This apparently worse response rate to chemotherapy after failed hormone therapy has also been noted in metastatic disease (Swenerton et al, 1979). Impaired response to chemotherapy in untreated ER-moderate/ -rich tumours has been previously noted (Bonadonna et al, 1990;Mauriac et al, 1991;Belembaogo et al, 1992). However, the known effects of hormone therapy upon breast cancer could further prejudice the subsequent response to chemotherapy.…”
Section: Response To Primary Hormone Therapymentioning
confidence: 96%
“…Thirteen (27.6%) had a complete regression. Others (Bonadonna et al, 1990) In premenopausal women with advanced breast cancer LHRH agonists will reduce serum oestradiol levels to the equivalent of the menopause or surgical oophorectomy (Dixon et al, 1990). These agents have an indirect action by reducing peripheral hormones rather than acting directly on LHRH receptors on the tumour (Harris et al, 1989).…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…References [1][2][3][4] Studies comparing neoadjuvant with adjuvant chemotherapy have shown that while disease-free, progression-free and overall survival are not changed by the timing of treatment, better outcomes are seen in patients who respond to neoadjuvant therapy [5][6][7]. These results highlight a key benefit of neoadjuvant therapy, the use of response to predict long-term outcome.…”
Section: Introductionmentioning
confidence: 99%